Charles Cullin, purser for the Steamboat VICTORIAN, in the Yukon Dock Company office, Dawson, Yukon Territory, 1900. - University of Washington Libraries. Special Collections Division
PH Coll 246.228 [Meed journal: "Chas Cullin, purser Str "Victorian", C.D. Co."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number